Penyiapan Pondasi dan Lantai Bangunan Utama Pengolahan Sampah di Dukuh Ngipikrejo II, Desa Banjararum, Kabupaten Kulonprogo - Iman Haryanto; Hotma P Sulistyadi; Syaukat Ali; Wiryanta Wiryanta; Edi Kurniadi; Agus Kurniawan (Jurnal Pengabdian dan Pengembangan Masyarakat, 2018)
Banjararum village does not have solid waste processing facility (“tempat pengolahan sampah” atau TPS) yet. The community service activity program aims to design TPS area site plan, TPS building (especially foundation and floor), and carry out the construction work. The building is located at village property site and includes area of 1000 m2. The work activities include location survey, surveying, site plan preparation, review and finalizing of site plan by team and village government partner, land clearing, bouwplank fixing, cut work, foundation construction, soil filling for floor levelling, construction of other building elements (column, wall, roof), tile fixing, and reporting. Technical data are consisted: floor area by dimension of 11´6 m, three maturity pools by dimension 3.5´4 m per pool, continuous river stone foundation (by dimension of height, base width, and top width of 0,6´0,6´0,3 m) and a layer beneath foundation made by river sands and stones. Village government partner assists team work through labor and material procurement and carry out daily supervising.